Triglyceride and Triglyceride-Rich Lipoproteins in Atherosclerosis - Zhang, Bai-Hui; Yin, Fan; Qiao, Ya-Nan; Guo, Shou-Dong (Frontiers in Molecular Biosciences, 2022)
Cardiovascular diseases (CVDs) are still the leading cause of death globally, and atherosclerosis is the main pathological basis of CVDs. Low-density lipoprotein cholesterol (LDL-C) is a strong causal factor of atherosclerosis. However, the first-line lipid-lowering drugs, statins, only reduce approximately 30% of the CVD risk. Of note, atherosclerotic CVD (ASCVD) cannot be eliminated in a great number of patients even their LDL-C levels meet the recommended clinical goals. Previously, whether the elevated plasma level of triglyceride is causally associated with ASCVD has been controversial. Recent genetic and epidemiological studies have demonstrated that triglyceride and triglyceride-rich lipoprotein (TGRL) are the main causal risk factor of the residual ASCVD. TGRLs and their metabolites can promote atherosclerosis via modulating inflammation, oxidative stress, and formation of foam cells. In this article, we will make a short review of TG and TGRL metabolism, display evidence of association between TG and ASCVD, summarize the atherogenic factors of TGRLs and their metabolites, and discuss the current findings and advances in TG-lowering therapies. This review provides information useful for the researchers in the field of CVD as well as for pharmacologists and clinicians.